Implementation of the Semi-Fowler Position to Improve Airway Clearance in Preschool Children with Acute Upper Respiratory Tract Infection (URTI) at Buton Regional Hospital: A Case Study - Sri Resky Mustafa; Sarti Wali; Nurjannah (Kiara Group, 2026)
Background: Acute Respiratory Infection (ARI) is a disease affecting the respiratory system caused by microorganisms. This condition can lead to airway obstruction, resulting in increased sputum accumulation in the bronchi and alveoli, as well as shortness of breath. If not promptly managed, ARI may progress to hypoxia. One nursing intervention to improve airway clearance is airway management through the semi-Fowler position. Objective: This study aimed to identify the improvement of airway clearance in a child with ARI who received airway management intervention. Methods: This study employed a descriptive design in the form of a case study involving one pediatric patient diagnosed with ARI. The instruments used included nursing care documentation sheets, a standard operating procedure (SOP) for semi-Fowler positioning, and observation sheets. The intervention was conducted for three days, twice daily (morning and afternoon), with a duration of 15 minutes per session. Results: After the implementation of the semi-Fowler position and the administration of warm fluids, the patient showed improvement, indicated by a respiratory rate of 26 breaths per minute, reduced wheezing sounds, a more regular breathing pattern, and the ability to expectorate sputum. Conclusion: The application of the semi-Fowler position effectively improved airway clearance in a child with Acute Respiratory Infection